History of Inter-Ethnic Relations in Bungorna,Mt. Elgon and Trans Nzoia Districts, 1875-1997 - (:unkn) unknown (My University, 2000)
This study recorgnises the significance of amity in ethnic relations in the development quests ofthe African continent. Inter-ethnic relations in this part of the world a:e constrained by various problems. The manifestations of such constrained relations in the form of co-operation, inter-dependence, suspicion and tension influence the nature of political discourses of identity. In certain cases the ethnic relations have been so bad that they have led to tragic consequences in parts of Africa. In other cases cordial inter-ethnic or intra-ethnic relations have resulted in peoples' economic growth, political stability as well as their social development. All these aspects are very interesting.Rather than set out to study inter-ethnic and intra-ethnic relations in the whole of Africa or Kenya, this study is limited to a region which covers mainly Bungonia, Mt Elgon and (the-part of Saboti Division of) Trans Nzoia districts. Major issues which are investigated include inter-ethnic and intra-ethnic interactions and their implications on the inhabitants' perception of nationhood. It is argued that inter- and intra-ethnic relations in the region under study are not only complex but also subtle to the extent that cooperation, interdependence and conflicts occurred either within specific;. ethnic or sub-ethnic composition as well as across ethnic confines. Furthermore, some skewed focus on inter-ethnic relations often lead to the weakening of nationhood as well as statehood as some political discourses of identity undermine the convergences apparently produced and reproduced by the nationalist ideology.The theoretical paradigm employed in this study considers the various changes traceable in inter-ethnic relations, notably the conflict theoretical construct. This is largely a sociologicaltheoiy, however, its sociological orientation is off loaded to give allowance for inclusion of historical imperatives and discourse in its scope. Although the restructuring of
Keywords: African Research